1983
DOI: 10.1080/00049538308255064
|View full text |Cite
|
Sign up to set email alerts
|

Taste intensity and the case of exponents greater than 1

Abstract: The magnitude estimation of taste intensity has often produced exponents greater than 1, suggesting that the perceived intensity of some taste stimuli increases at a faster rate than does stimulus concentration, i.e., the psychophysical functions are positively accelerating. However, a reanalysis of published data reveals that when these magnitude scales are replotted in linear coordinates, instead of the conventional log-log form, there is often no evidence of positive acceleration and the numerical value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Definitions aside, however, Figure 7 shows how supplemental action can be accounted for in terms of the addition (or near addition) of negatively accelerated psychophysical functions—that is, in terms of compression rather than expansion. If the psychophysical functions of taste stimuli generally tend toward negative acceleration, as has been suggested elsewhere (McBride, 1982b, 1983c), and if the present pattern also applies to other binary mixtures, supplemental action will commonly occur. In support of this reasoning, Kamen (1959) noted supplemental action with mixtures of sucrose and calcium cyclamate, and Homler (1984) with mixtures of aspartame and various other sweeteners (see also Yamaguchi, Yoshikawa, Ikeda, & Ninomiya, 1970).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Definitions aside, however, Figure 7 shows how supplemental action can be accounted for in terms of the addition (or near addition) of negatively accelerated psychophysical functions—that is, in terms of compression rather than expansion. If the psychophysical functions of taste stimuli generally tend toward negative acceleration, as has been suggested elsewhere (McBride, 1982b, 1983c), and if the present pattern also applies to other binary mixtures, supplemental action will commonly occur. In support of this reasoning, Kamen (1959) noted supplemental action with mixtures of sucrose and calcium cyclamate, and Homler (1984) with mixtures of aspartame and various other sweeteners (see also Yamaguchi, Yoshikawa, Ikeda, & Ninomiya, 1970).…”
Section: Discussionsupporting
confidence: 72%
“…Integration psychophysics, in contrast, does respect this possibility. One other major advantage of the present paradigm is that there is no fitting of theoretical curves (e.g., power functions) to the mixture and its components, a practice that can sometimes be problematical in itself (McBride, 1983c, McBride & Anderson, 1986). Instead, information on mixture perception is available from inspection of the factorial plot.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects, who were not permitted to use zeros even for the sample with 0 g/L of added caffeine, might have had to use very small fractions thereby distorting the psychophysical function near the origin and yielding a poor fit of the ME data by a power function. Several other investigators have reported magnitude estimates which gave poor fits to a power function (O'Mahony and Heintz 1981; Giovanni and Pangborn 1981;Powers et al 1981;McBride 1983). Although opinions vary on the influence of judge training on ability to generate whole-number proportions, we concur with Teghtsoonian and Teghtsoonian (1971), Beck and Shaw (1975) and Robinson (1976) that many judges require practice in use of ratios to scale sensation in order to generate numbers which represent perceptual ratios.…”
Section: Function Fitting Of Intensity Estimates Obtained By Categorysupporting
confidence: 74%
“…This note is directed at a problem in data analysis, and is not intended to address the issue of the correct exponent for electric shock. It simply demonstrates that the shape of a psychophysical function is not necessarily reflected by its exponent, and stands alongside other related questioning of power functions in psychophysics (Carterette & Anderson, 1979;Coleman, Graf, & AIf, 1981;McBride, 1983;Myers, 1982).…”
mentioning
confidence: 87%
“…
The results of magnitude estimation studies are customarily presented in the form of log-log plots. However, a reanalysis of taste data (McBride, 1983) has revealed that such plots can be seriously misleading. This note reports a further example in a dimerent modality.Stevens.
…”
mentioning
confidence: 99%